The Focaliser Focalised in King Vidor’s The Crowd (1928) - Celestino Deleyto (Miscelánea: A Journal of English and American Studies, 1993)
The concepts of internal and external focalisation, as described by Bal (1985), Rimmon-Kenan (1983) and others, provide, with certain variations, a powerful way to approach, from a rigorous narratological standpoint, some of the most hotly debated issues in film theory in the past twenty years: spectator manipulation and subject positioning in classical and non-classical films through the activation of mechanisms related to the gaze. This analysis of The Crowd (King Vidor 1928) attempts an interpretation of the film through the exploration of patterns of external and internal focalisation in two key scenes of the film. This is related to the use of narrative time by the text 2 and the complex network of tensions, parallelisms and contrasts established at several narrative levels. As a conclusion, it is suggested that the narratively unmotivated disavowal of internal focalisation in one of these scenes works as a metaphor for the process of deterioration undergone by the protagonist in the course of the film.